Taking a knee: Haunted memetic counter-activism. (August 2022) - Lennox, Solomon
In May 2020, the world witnessed Derek Chauvin, a serving White police officer, murder George Floyd, a Black American male. A video of the murder, shot by Darnella Frazier, documented Chauvin kneeling on Floyd's neck for a little under eight minutes. The video served as a call to action with protests erupting throughout the summer of 2020 across the USA. Activists took to the streets demanding an end to police brutality and systemic racism. The act of kneeling became a recurrent symbol of these protests. This article specifically focuses on instances where police officers have taken the knee opposite protesters. The author argues that, within this context, kneeling is a memetic performance; it is a unit of cultural information passed on through repetition and mutation. Through mutation (repetition with difference), the symbolic meaning of the act changes. In the case of police officers kneeling opposite protesters, the act purportedly symbolizes moments of solidarity and understanding between the two sides. Much like the video that inspired the protests, instances of officers kneeling opposite protesters were captured, disseminated via social media and went viral. The stillness of these moments promised hope for movement towards a more equitable and humane future. But these images serve as a form of dirty data as they document a future yet to materialize. To this end, the act of kneeling is a haunted gesture, serving as a form of counter-activism. The act of kneeling by police officers, irrespective of the intentions of the individuals involved, does not solicit an encounter with the ghosts of police brutality and systemic racism. Rather the act, as a mutated form of activism, simultaneously disrupts the atmosphere of protests and reclaims narratives about police conduct, without enacting meaningful change.